A Physio-Logging Journey: Heart Rates of the Emperor Penguin and Blue Whale - Ponganis, Paul J. (Frontiers in Physiology, 2021)
Physio-logging has the potential to explore the processes that underlie the dive behavior and ecology of marine mammals and seabirds, as well as evaluate their adaptability to environmental change and other stressors. Regulation of heart rate lies at the core of the physiological processes that determine dive capacity and performance. The bio-logging of heart rate in unrestrained animals diving at sea was infeasible, even unimaginable in the mid-1970s. To provide a historical perspective, I review my 40-year experience in the development of heart rate physio-loggers and the evolution of a digital electrocardiogram (ECG) recorder that is still in use today. I highlight documentation of the ECG and the interpretation of heart rate profiles in the largest of avian and mammalian divers, the emperor penguin and blue whale.